Digital Adoption in Informal Micro-Property Management: A TAM–Lean–BMC Conceptual Framework and Research Agenda - Esri Hestiningtyas; Rahadi, Raden Aswin (Integrasi Sains Media, 2026)
This conceptual study tackles the digital-adoption gap in Jakarta's kos-kosan boarding-house rooms, where landlords managing 5–20 units still juggle paper ledgers despite near-universal smartphone and WhatsApp use. Guided by the Technology Acceptance Model (TAM), Lean Start-up logic, and the Business Model Canvas (BMC), this research develops an integrated theoretical framework that explains behavioral hesitancy, sequences low-risk Minimum Viable Product (MVP) iterations, and pinpoints the